Dimensions of academic procrastination and its relationship to perceived self-efficacy among first-year undergraduate students at King Saud University - Boriek, Elsayed Ramadan (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the level of dimensions of academic procrastination and its relationship to perceived self-efficacy among first-year undergraduate students at King Saud University. The researcher used the descriptive correlational method, The study sample consisted of (202) first-year undergraduate students at King Saud University, and measures of perceived self-efficacy and academic procrastination (prepared/researcher) were applied to them. The results showed; The behavior of academic retardation among first-year students at King Saud University obtained a total average of (2.17), i.e. a (low) level, and with regard to the dimensions; The time management got the highest average (4.21) at the (high) level, then the psychological factors got an average (3.14) at the (medium) level, and the social factors got an average (2.20) at the (low) level, while the perceived self-efficacy got an average total ability (3.62), that is, a (high) level. The results also revealed an inverse linear relationship between academic procrastination and perceived self-efficacy, and perceived self-efficacy explained more than (%27) of the variance in academic procrastination. Based on the results of the study, the researcher recommended organizing workshops and training courses to raise awareness of the seriousness of academic procrastination, and to reconsider student tasks and assignments so that they do not constitute pressure that leads to academic procrastination.
Keywords: Academic Procrastination; perceived self-efficacy; first-year undergraduate